Universal Dependencies for 19th-Century Nheengatu from the Lower Amazon Region - Alexandre, Dominick Maia; Alencar, Leonel Figueiredo de (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2025)
We present the morphosyntactic annotation of Nheengatu as spoken in the 19th century in the Lower Amazon region. The annotated data expand the UD Nheengatu-CompLin treebank, the first for Nheengatu in the Universal Dependencies project, by incorporating forms and syntactic patterns characteristic of that region and time. We describe the corpus source, the orthographic normalization process, and the main annotation strategies used. So far, 345 sentences have been annotated, with 310 already integrated into the current version of the treebank. This historical data annotation enhances the lexical and morphosyntactic coverage, supporting the documentation and computational modeling of Nheengatu.